(untitled) (Південний архів (історичні науки), 2022)
Purpose. This article describes the situation in Ukraine with trade and economic education in the 1920s, namely the issue of organizing the scientific and pedagogical work of cooperative colleges. Methods. The research methodology is based on the principles of historicism, systematicity, scientificity, verification, authorial objectivity, moderate constructivism, as well as the use of general scientific (analysis, synthesis, generalization) and special historical (historical-systemic, historical-typological) methods. Results. The article presents the basic statistical data on entrants, as well as the basic social composition of students and their living and learning conditions. The paper emphasizes the lack of commercial specialists and the difficult financial situation of students at that time. The main disciplines taught in three courses of technical schools are presented in detail. Attention is paid to the problems of state funding and emphasis is placed on financial support from economic and commercial organizations. The aim of the article is to reveal the tasks and goals that were set before the trade and economic education of the party and the role of institutions in the development of trade and economic education in the 1920s. The authors emphasize the role of trade and economic education in the birth of a new commercial and proletarian intelligentsia. The article presents the main organizational aspects of Odessa, Kharkiv, Smilyansk cooperative technical schools, reveals the tasks and goals set for the heads of technical schools. It should also be noted that this topic is relevant, as in Ukraine there are only fragmentary studies of trade and economic education in the 1920s. On the basis of archival documents, it is possible to trace the history of cooperative technical schools and comment on the main goals of the government to create a new base of trade and economic education and new specialists in the field of trade. Conclusions. The system of trade and economic education had a clear goal – to proletarianize education and involve the peasant masses in the promotion of cooperation. According to the information contained in the archival documents developed by the authors, it can be stated that cooperative technical schools served as an additional link in the development of cooperative learning and were designed to connect the village with the cooperative. At the same time, the Soviet authorities included the training and retraining of the teaching staff, the expansion of the number of commercial specialists, the increase in the number of students of proletarian and peasant origin, the stimulation of practical work, and so on.